Chemical characterization of the polar antibacterial fraction of the ethanol extract from Rosmarinus officinalis. (15th May 2021) - Zhong, Xiangjian; Wang, Xin; Zhou, Na; Li, Jinjie; Liu, Jiachen; Yue, Jianyu; Hao, Xiaomeng; Gan, Maoluo; Lin, Pengcheng; Shang, Xiaoya
Highlights: A non-volatile polar fraction of rosemary with strong antibacterial activity was found. Rapid chemical characterization of the antibacterial fraction based on high resolution mass spectrometry. Two new diterpenes and six known compounds were found in rosemary for the first time. Most isolated compounds showed significant antibacterial activity. Abstract: Rosmarinus officinalis L. has been widely used as a spice to extend the shelf life of foods. Most studies in the literature indicate that its essential oil is its major antibacterial component. In this study, a polar fraction from rosemary exhibited considerably stronger antibacterial activity against Bacillus subtilis than its essential oil. Guided by rapid characterization of the chemical compositions based on UPLC-Orbitrap-MS/MS, further investigation resulted in the isolation and identification of sixteen compounds. Among them, two new and six known compounds were identified in rosemary for the first time. Most isolated compounds exhibited significant antibacterial activities with minimum inhibitory concentration values of 2–128 μg/mL; however, these activities were weaker than that of the polar fraction. Thus, the polar fraction demonstrated a promising potential to serve as a food additive, as an alternative to the essential oil, because of its stronger antibacterial activity.